2020
DOI: 10.3390/ijerph18010167
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Action Research Applied to an Ear, Nose, and Throat Specialty Service Redesign in Remote Australia: A Mixed-Methods Study of Key Stakeholder Perspectives

Abstract: This mixed-methods study reports on the key stakeholders’ perspectives on the ear, nose, and throat (ENT) service redesign in remote Australia, using a participatory action research (PAR) approach. A primary health care (PHC) clinician survey was conducted to assess local needs and possible educational gaps in clinical knowledge. This was followed by an internal stakeholder forum and a follow-up survey with Torres and Cape Hospital and Health Service staff to gain their perspectives on current service delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Projects successfully increased the number of children screened 3,5,7,29,32 and identified telehealth as feasible and relatively accurate for clinical diagnosis and management of OM. 30,35,36,[46][47][48][51][52][53] As documented in the literature, studies consistently reported high levels (ranging from 42% to 64%) of OM among Indigenous children. 26,27,33,42,49 Some included studies reported increased OM knowledge and correct diagnosis resulted in improved child behaviour, 22,31,38,43 school performance, 22,38 family life 22,38 and physical health.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…Projects successfully increased the number of children screened 3,5,7,29,32 and identified telehealth as feasible and relatively accurate for clinical diagnosis and management of OM. 30,35,36,[46][47][48][51][52][53] As documented in the literature, studies consistently reported high levels (ranging from 42% to 64%) of OM among Indigenous children. 26,27,33,42,49 Some included studies reported increased OM knowledge and correct diagnosis resulted in improved child behaviour, 22,31,38,43 school performance, 22,38 family life 22,38 and physical health.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
“…26,27,33,42,49 Some included studies reported increased OM knowledge and correct diagnosis resulted in improved child behaviour, 22,31,38,43 school performance, 22,38 family life 22,38 and physical health. 43 Three studies primarily focused on strengthening ear health screening skills and confidence for IHWs 9,15,51 and one study stressed the importance of providing specialised training for non-Indigenous Health Workers to generate a better understanding of Indigenous health contexts. 35 Challenges research teams faced in maintaining the success of their screening programs included the resource-intensive nature of programs, 30 high healthcare and teaching staff turnover, 35,40 limited OM knowledge in communities and schools, 39,40 service accessibility 35,39 and limited evaluation methods.…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Primary healthcare can play a role in reducing referrals to tertiary care. So, they should have an improved local service as stated in [13] to reduce the workload of tertiary healthcare centers. The accessibility of primary healthcare makes it the prime cornerstone of the healthcare delivery system.…”
Section: Role Of Urgent Referral Clinicmentioning
confidence: 99%